POLITICAL ECONOMIC CORRELATION WITH POLITICS IN THE FIELD OF CRIMINAL LAW ENFORCEMENT - Rambey, Guntur (Proceeding International Seminar of Islamic Studies, 2023)
Activities in the economic sector require law as a basis and at the same time policy legitimacy to achieve national goals so that it is a necessity if the two disciplines of economics and law are seen as unable to ally in advancing the Indonesian people. Furthermore, according to Romli Atmasasmita, an economic analysis of law that uses the principle of maximization of balance (equilibrum) and efficiency (efficiency) with the